The Effect of Guidance regarding Home Exercise and ADL on Adolescent Females Suffering from Adverse Effects after HPV Vaccination in Japanese Multidisciplinary Pain Centers. (18th April 2016) - Ushida, Takahiro; Shibata, Masahiko; Kitahara, Masaki; Yabuki, Shoji; Sumitani, Masahiko; Murakami, Takanori; Iseki, Masako; Hosoi, Masako; Shiokawa, Hiroaki; Tetsunaga, Tomoko; Nishie, Hiroyuki; Fukui, Sei; et al.
Abstract : Background . Two prophylactic papillomavirus (HPV) vaccines have been available for primary prevention of cervical cancer. Although serious adverse effects (AE) were rare, more than 230 women have been suffering from severe AEs such as persistent pain and headache in Japan. Our research group started to treat adolescent females suffering from the AEs. Objective . To survey the characteristics of and the effects of cognitive behavioral therapy on adolescent female suffering from the AEs in Japanese multidisciplinary pain centers. Methods . One hundred and forty-five patients suffering from the AEs were reviewed retrospectively and 105 patients of them were provided guidance on home exercise and activities of daily living based partially on a cognitive-behavioral approach. The intensity of pain was rated by the patients using a numerical rating scale (NRS). Furthermore, the Hospital Anxiety and Depression Scale (HADS) and the Pain Catastrophizing Scale (PCS) were used. Results . Eighty out of the 105 patients who received the guidance were followed up, 10 displayed a marked improvement, and 43 showed some improvement. Conclusions . Guidance on home exercise and activities of daily living based on a cognitive-behavioral approach alleviated the AEs that women suffered from after HPV vaccination in Japan.